Mental health labelling, women’s autonomy and social inclusion in Indian marital settings: a conceptual framework - Alka Singh Bhatt; Ramya Singh; Ridhima Bhalla; Sharad Dixit (Mental Health and Social Inclusion, 2026)
Purpose This paper aims to examine how mental health labelling within Indian marital settings may influence women’s autonomy and social inclusion. It argues that labels attached to women’s emotional distress, psychological vulnerability or help-seeking behaviour may operate not only as descriptions of mental health concerns but also as social mechanisms that shape marital power, family decision-making and community participation. Design/methodology/approach The paper adopts a conceptual approach based on a structured narrative synthesis of literature related to mental health labelling, stigma, gendered marital relations, women’s autonomy, help-seeking and social inclusion. It develops an integrated framework to explain how mental health labelling may affect women’s dignity, agency and participation within family and community life. Findings The paper proposes that mental health labelling may reduce women’s autonomy when it is associated with stigma, mistrust, marital control and social withdrawal. The framework suggests that labelling can affect decision-making power, mobility, financial voice, emotional expression, reproductive choices and access to support. However, family support, community awareness, counselling access and help-seeking confidence may reduce the exclusionary effects of labelling and promote recovery-orientated inclusion. Originality/value The paper contributes to mental health and social inclusion scholarship by linking mental health labelling to women’s autonomy in Indian marital settings. It offers a culturally grounded framework useful for researchers, counsellors, social workers, women’s organisations and community mental health practitioners.